(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Communication is one of the most important aspects of daily life. English is a well-established language, and a lot of research has been done on the language and its grammatical constructs. However, for the differently abled people, with respect to communication, the medium of communication is sign language. This paper presents a model for converting English text to Indian sign language (ISL). The input is any English sentence which is parsed using the Stanford parser. ISL, has its own grammatical syntax. Hence, the parsed sentence has to be reordered and converted, into a sentence that is compatible with ISL. From this reordered sentence, an elimination module, removes all the unnecessary words, which are not a part of the ISL vocabulary. ISL signs are always made in present tense; hence a lemmatization module has been added to convert the words into their simplest forms. Once, this is done, we obtain the final ‘ISL sentence’, from which each word is mapped to its corresponding video. These videos contain individual ISL signs. Finally, all the videos of that sentence is concatenated and displayed in sequence. The proposed system provides an innovative way to serve the needs of the differently abled by acting as an excellent translation medium during conversations between people. The system can also function as an exceptional teaching aid.